Tree species effects on nutrient cycling and soil biota: A feedback mechanism favouring species coexistence - Aponte, Cristina; García, Luis V.; Marañón, Teodoro (Forest Ecology and Management, 2013)
We synthesise a series of independent but integrated studies on the functioning of a mixed Mediterra- nean oak forest to demonstrate the tree–soil interactions underpinning a positive feedback process that sustains the coexistence of two oak species. The studies focused on the foliar functional traits, plant regeneration patterns, biogeochemical cycles, soil microbial biomass and ectomycorrhizal (ECM) fungal diversity associated with the co-dominant evergreen Quercus suber and deciduous Quercus canariensis in a Mediterranean forest in southern Spain. Foliar attributes differed between oak species, with Q. canariensis having higher nutrient content and lower carbon to nutrient ratios and leaf mass per area than Q. suber. These attributes reflected their distinct resource use strategies and adaptation to high and low resource-availability environ- ments, respectively. Leaf-fall nutrient concentrations were higher in Q. canariensis than in Q. suber and were correlated with concentrations in the fresh leaves. Leaf-fall nutrient concentrations influ- enced nutrient return, leaf-fall decay rate and the proportion of nutrients released from decomposing leaf-fall, all of which were higher for Q. canariensis than for Q. suber. This generated a differential net nutrient input into the soil that led to increased soil nutrient concentrations under the canopy of Q. canariensis as compared to Q. suber. The fraction of slowly decomposing leaf-fall that builds up soil organic matter was higher for Q. canariensis, further raising the nutrient and moisture retention of its soils. Differences between species in soil properties disappeared with increasing soil depth, which was consistent with the hypothesised leaf-fall-mediated effect. Tree-species-generated changes in soil properties had further impacts on soil organisms. Soil microbial biomass (Cmic) and nutrients (Nmic, Pmic) were higher under Q. canariensis than under Q. suber and were positively related to soil mois- ture content and substrate availability (particularly soil N). The composition of the ECM fungal com- munity shifted between the two oaks in response to changes in the soil properties, particularly soil Ca and pH. Lower ECM phylogenetic diversity and higher abundance of mycorrhizal species with sapro- phytic abilities were related to the greater soil fertility under Q. canariensis. Overall, the two oak spe- cies generated soil conditions that aligned with their resource-use strategies and would enhance their own competitive capabilities, potentially creating a positive feedback. The two Quercus created soil spatial heterogeneity that could enable their coexistence through spatial niche partitioning. This study demonstrates the critical role of aboveground-belowground interactions underpinning forest commu- nity composition. 
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Feedback processes; Microbial biomass; Mycorrhizal fungi; nutrient cycling; Plant–soil interactions; Quercus

Spatial patterns of soil pathogens in declining Mediterranean forests: implications for tree species regeneration. - Gómez-Aparicio, LORENA; Ibáñez, Beatriz; Serrano, María S.; De Vita, Paolo; Avila, José M.; Pérez-Ramos, Ignacio M.; García, Luis V.; Esperanza Sánchez, M.; Marañón, Teodoro (The New phytologist, 2012)
Soil-borne pathogens are a key component of the belowground community because of the significance of their ecological and socio-economic impacts. However, very little is known about the complexity of their distribution patterns in natural systems. Here, we explored the patterns, causes and ecological consequences of spatial variability in pathogen abundance in Mediterranean forests affected by oak decline. We used spatially explicit neighborhood models to predict the abundance of soil-borne pathogen species (Phytophthora cinnamomi, Pythium spiculum and Pythium spp.) as a function of local abiotic conditions (soil texture) and the characteristics of the tree and shrub neighborhoods (species composition, size and health status). The implications of pathogen abundance for tree seedling performance were explored by conducting a sowing experiment in the same locations in which pathogen abundance was quantified. Pathogen abundance in the forest soil was not randomly distributed, but exhibited spatially predictable patterns influenced by both abiotic and, particularly, biotic factors (tree and shrub species). Pathogen abundance reduced seedling emergence and survival, but not in all sites or tree species. Our findings suggest that heterogeneous spatial patterns of pathogen abundance at fine spatial scale can be important for the dynamics and restoration of declining Mediterranean forests.
The following values have no corresponding Zotero field: accession-num: 22428751
Keywords: Biological; Forest decline; Host-Pathogen Interactions; Mediterranean Region; Models; neighborhood models; Phytophthora; Phytophthora: physiology; Pythium; Pythium: physiology; Quercus; Quercus suber; Quercus: microbiology; regeneration dynamics; Seedling; Seedling: microbiology; Soil Microbiology; soil texture; soil-borne pathogens; species coexistence

Tree Species Effect on Litter Decomposition and Nutrient Release in Mediterranean Oak Forests Changes Over Time - Aponte, Cristina; García, Luis V.; Marañón, Teodoro (Ecosystems, 2012)
ree species can affect the decomposition process through the quality of their leaf fall and through the species-speciﬁc conditions that they generate in their environment. We compared the relative importance of these effects in a 2-year experiment. Litterbags containing leaf litter of the winter-deciduous Quercus canariensis, the evergreen Q. suber and mixed litter were incubated beneath distinct plant covers. We measured litter carbon loss, 9 macro- and micronutrients and 18 soil chemical, physical and biological parameters of the incubation environment. Tree species affected decay dynamics through their litter quality and, to a lesser extent, through the induced environmental conditions. The deciduous litter showed a faster initial decomposition but left a larger fraction of slow decomposable biomass compared with the perennial litter; in contrast the deciduous environment impeded early decomposition while promoting further carbon loss in the latter decay stages. The interaction of these effects led to a negative litter–environment interaction contradicting the home-ﬁeld advantage hypothesis. Leaf litter N, Ca and Mn as well as soil N, P and soil moisture were the best predictors for decomposition rates. Litter N and Ca exerted counteractive effects in early versus late decay stages; Mn was the best predictor for the decomposition limit value, that is, the fraction of slowly decomposable biomass at the later stage of decomposition; P and soil moisture showed a constant and positive relation with carbon loss. The deciduous oak litter had a higher initial nutrient content and released its nutrients faster and in a higher proportion than the perennial oak litter, signiﬁcantly increasing soil fertility beneath its canopy. Our ﬁndings provide further insights into the factors that control the early and late stages of the decomposition process and reveal potential mechanisms underlying tree species inﬂuence on litter decay rate, carbon accumulation and nutrient cycling.
Keywords: decomposition limit value; Lignin; litter chemistry; litterbag; Plant–soil interactions; Quercus; Soil fertility